Effectiveness and Public Perception of Synthetic and Natural-Based Mosquito Repellents Against Aedes aegypti in Indonesia - Ahmad, Intan; Amalia, Riska; Yusmalinar, Sri (School of Life Sciences and Technology, Institut Teknologi Bandung, 2025)
Since 1968, dengue fever cases in Indonesia have persisted despite various vector control efforts. One of the most common and accessible methods of personal protection is the use of mosquito repellents. This study evaluated public perceptions of mosquitoes and repellents, their willingness to pay (WTP) for these products, and the efficacy of synthetic and natural-based repellents against Aedes aegypti, considering variations in mosquito strain and age. A Knowledge, Attitude, and Practices (KAP) analysis was conducted to assess public understanding and behaviors, utilizing the Analytical Hierarchy Process (AHP) and SWOT-AHP. Repellent efficacy was tested using the arm-in-cage method based on WHO guidelines, involving four mosquito strains (BORA, BDG, TSK, TGR) and three age groups (5, 10, 15 days). The KAP analysis revealed high public awareness but limited translation into effective practices due to differing perceptions and low personal responsibility for dengue prevention. Natural-based repellents were preferred, scoring 3.40 out of 5, with WTP ranging from IDR 20,000–40,000. However, only synthetic repellents containing DEET provided 90% protection for six hours, while natural-based repellents offered less than 60% protection in the first hour. Strain variation significantly affected repellency, with TSK showing the highest repellency, while BORA and BDG exhibited similar trends. Although 10-day-old mosquitoes were more sensitive to repellents, age variation did not consistently influence repellency. These findings highlight the need for improved education campaigns, tailored repellent formulations, and localized testing to enhance public protection against mosquito bites and dengue transmission.